(untitled) (gjstudies, 2024)
This research investigates the transformative impact of recent regulatory changeson corporate accounting practices, employing a novel methodological framework thatintegrates computational text analysis with network theory to map the diffusion of regulatory influence across organizational structures. Unlike traditional compliance studies that focus on binary adherence metrics, this paper introduces a dynamic systemsapproach that conceptualizes regulatory changes as information cascades propagatingthrough interconnected accounting subsystems. We analyze three major regulatoryshifts implemented between 2020-2024 across 450 multinational corporations, examining not only procedural adaptations but also the cognitive and organizational reconfigurations that emerge in response to regulatory pressure. Our methodology combinesnatural language processing of accounting policy documents with agent-based modeling of decision-making processes within accounting departments, revealing previouslyundocumented patterns of regulatory absorption and resistance. The findings demonstrate that regulatory influence operates through three distinct channels: direct compliance pathways, indirect network effects through industry associations, and emergentadaptive behaviors that sometimes subvert regulatory intent. We identify a paradoxicalphenomenon wherein increased regulatory specificity in certain domains (particularlyrevenue recognition and environmental disclosures) correlates with decreased uniformity in implementation approaches, suggesting that organizations develop increasinglysophisticated regulatory arbitrage strategies even as they demonstrate surface-levelcompliance. The research contributes to accounting information systems literatureby providing a multi-dimensional framework for understanding regulatory impact thatmoves beyond check-box compliance to examine how regulations reshape organizationalcognition, communication patterns, and innovation trajectories within accounting functions. Our computational approach reveals that the most significant transformationsoccur not in formal reporting outputs but in the internal decision-support systemsand data governance structures that underpin accounting practices, suggesting thatfuture regulatory assessments should focus on these infrastructural elements rather than surface-level disclosures.